3D-printed individualized tooth-borne tissue retraction devices compared to conventional dental splints for head and neck cancer radiotherapy: a randomized controlled trial - Held, Thomas; Herpel, Christopher; Schwindling, Franz Sebastian; Christ, Leo; Uzun-Lang, Kristin; Regnery, Sebastian; Eichkorn, Tanja; Hommertgen, Adriane; Jäkel, Cornelia; Krisam, Johannes; Moratin, Julius; Mrosek, Jan Bernd; et al. (Radiation oncology, 2021)
Despite modern treatment techniques, radiotherapy (RT) in patients with head and neck cancer (HNC) may be associated with high rates of acute and late treatment-related toxicity. The most effective approach to reduce sequelae after RT is to avoid as best as possible healthy tissues and organs at risk from the radiation target volume. Even small geometric changes can lead to a significant dose reduction in normal tissue and better treatment tolerability. The major objective of the current study is to investigate 3D printed, tooth-borne tissue retraction devices (TRDs) compared to conventional dental splints for head and neck RT.
Gesehen am 21.05.2021